Realizing Indonesia as a Global Maritime Fulcrum - Artha C. Rosevina Anak Ampun; Widodo; Panji Suwarno; Pujo Widodo; Herlina Juni Risma Saragih; Andri Octapianus Purba (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The idea of the Global Maritime Fulcrum (GMF) becomes a maritime strategic approach. The government of President Jokowi with the vision of the GMF is determined to rebuild Indonesia's maritime glory. Maritime security is one of the key factors to guarantee the pillars of sovereignty and prosperity. A strong foundation for building Indonesia's vision as the GMF is the nation's geostrategic location and historical overview. The realization of Indonesia as the GMF has a strong foundation, both legal basis, historical review, and socio-economic strength. An important aspect to be developed in order to realize the GMF is the maritime and maritime economic aspects, as well as aspects that are components of governance. The transformation of the defense system, namely land, sea and air can support realizing Indonesia as a Maritime Fulcrum. The idea of realizing Indonesia as a GMF must have relevance between foreign policy and the geographical character of a country and assumptions about establishing the concept of making Indonesia a GMF.